2020
DOI: 10.1016/j.joule.2020.01.015
|View full text |Cite
|
Sign up to set email alerts
|

Mechanically Stacked, Two-Terminal Graphene-Based Perovskite/Silicon Tandem Solar Cell with Efficiency over 26%

Abstract: A novel configuration for high-performant perovskite/silicon tandem solar cells is demonstrated using a facile mechanical stacking of the sub-cells. The resulting champion perovskite/silicon tandem solar cell exhibits a stabilized efficiency of 25.9% over an active area of 1.43 cm 2 .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
115
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 149 publications
(125 citation statements)
references
References 89 publications
2
115
1
Order By: Relevance
“…[125,126] In this context, Lamanna et al reported a low power density (<0.40 W cm −2 ) deposition condition (1.1 × 10 −33 mbar, Ar) for the ITO upper layer on the organic HTMs to fabricate bufferlayer-free bifacial mesoscopic perovskite top cells. [127] The authors used a graphene doped TiO 2 as the electron transport material (ETM) to enhance the performance of the perovskite top cell, and the final champion tandem device demonstrated a 26.3% efficiency (25.9% stabilized) over an active area of 1.43 cm 2 . This 'soft' deposition technique is critical to simplify the process of bifacial PSCs.…”
Section: Transparent Electrodesmentioning
confidence: 99%
“…[125,126] In this context, Lamanna et al reported a low power density (<0.40 W cm −2 ) deposition condition (1.1 × 10 −33 mbar, Ar) for the ITO upper layer on the organic HTMs to fabricate bufferlayer-free bifacial mesoscopic perovskite top cells. [127] The authors used a graphene doped TiO 2 as the electron transport material (ETM) to enhance the performance of the perovskite top cell, and the final champion tandem device demonstrated a 26.3% efficiency (25.9% stabilized) over an active area of 1.43 cm 2 . This 'soft' deposition technique is critical to simplify the process of bifacial PSCs.…”
Section: Transparent Electrodesmentioning
confidence: 99%
“…Lamanna et al realized an inspiring combination of a heterojunction Si solar cell and a high temperatureprocessed perovskite solar cell by mechanical stacking in a 2-T configuration (Figure 8h). [151] To reduce parasitic absorption at the HTL/ITO interface, spiro-OMeTAD was substituted with PTAA, and graphene flakes were incorporated into the c-TiO and mesoporous TiO 2 of the ETL to enhance charge extraction with lowered series resistance. The mechanically stacked 2-T hybrid presented a matched current density of 18.81 mA cm −2 and a V oc of 1.8 V that almost equaled the sum of subcell V oc s. Consequently, for a reverse scan and an active area of 1.43 cm 2 , a high PCE of 26.3% and an FF of 77.5% were obtained.…”
Section: Mechanically Stacked Interconnectionmentioning
confidence: 99%
“…[5][6][7][8][9][10][11] The beneficial impact of graphene and related 2D materials in PSCs has been demonstrated both in mesoporous [12][13][14][15][16] and inverted planar structures, [17][18][19] as well as in their corresponding tandem systems. 20 Beyond graphene and its derivatives, various 2D material families have been tested including transition metal dichalcogenides, 21 MXenes, 13,22 phosphorene 23,24 and antimonene, 25 just to name a few. The high degree of structural and optoelectronic tunability of 2D materials renders them an ideal choice to form functional layers in PSCs.…”
Section: Introductionmentioning
confidence: 99%